2017
DOI: 10.1097/ijg.0000000000000687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uterine Fundal Pressure on Maternal Intraocular Pressure in Cesarean Delivery: Comparison of Regional and General Anesthesia

Abstract: In conclusion, fundal pressure may significantly increase the IOP, but the choice of anesthetic technique may not have any effect on IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
2
7
1
Order By: Relevance
“…Although it has been found that fundal pressure, in order to facilitate delivery during C-section, does cause a small increase in maternal IOP. 83 This is contrary to what was believed earlier, but there is no clinical evidence in support of these findings.…”
Section: Stage-wise Management Plancontrasting
confidence: 76%
“…Although it has been found that fundal pressure, in order to facilitate delivery during C-section, does cause a small increase in maternal IOP. 83 This is contrary to what was believed earlier, but there is no clinical evidence in support of these findings.…”
Section: Stage-wise Management Plancontrasting
confidence: 76%
“…Very few studies have been concerned with use of fundal pressure in CS. In study of Kurtay et al [6] they studied the Effect of Uterine Fundal…”
Section: Discussionmentioning
confidence: 99%
“…In a normal delivery, the mother facilitates delivery through the birth canal by the Valsalva maneuver (16). It has been observed that, this maneuver can increase IOP by the mechanism of increasing intrathoracic pressure followed by the jugular and orbital vein congestion (17). In addition, in some patients, holding their breath affects the IOP by increasing intrathecal pressure.…”
Section: Key Pointmentioning
confidence: 99%
“…Some obstacles to vaginal delivery may include myopia, retinal detachment, diabetic retinopathy and glaucoma (15). However, according to previous studies, there is no definite indication in the field of ophthalmology to determine the type of delivery (17), which concerns obstetricians treating women with eye diseases (10).…”
Section: Key Pointmentioning
confidence: 99%